Using the Maan -Whitney Test to Compare the Degree of Groundwater Pollution between Two Cities in Libya: Zliten and Sirt - Alteer, Fatima Ali; Ashmila, Alhadi Ragab; Alashhab, Bothayna Ebrahim (The 1st International Conference On Basic Sciences & Its Applictionss, 2024)
Nowadays, the Groundwater pollution is one of the important environmental problems, alongside many other pollution issues. This study aimed to highlight the significance of this issue due to its direct impact on environmental safety and human health. A comparison was made between two samples from different areas in Libya, Zliten and Sirte, by examine the important pollution indicators such as Total Dissolved Solids (TDS), Calcium (Ca), Chloride (Cl), Magnesium (Mg), and Electrical Conductivity (EC) in twenty wells from each city. Nonparametric Statistical tools were used for comparison, including the Mann-Whitney test. The findings revealed that there were significant differences in the averages of all indicators between Zliten and Sirte. The results also indicated that there was no significant statistical difference for Calcium between the two cities.
Keywords: Groundwater pollution; Normal testing; Nonparametric tests; Maan- Whitney tests; Correlation Coefficient